Influence of the pH on the Condensation of Tetravalent Cerium Cations in Association with [α‐SiW9O34]10– Leading to the Formation of a Ce6O4(OH)4 Core. Issue 34 (2nd November 2016) - Duval, Sylvain; Trivelli, Xavier; Roussel, Pascal; Loiseau, Thierry
Abstract : The reaction of Na10 [α‐SiW9 O34 ] with 4f tetravalent cerium cations in aqueous solution in the presence of sodium acetate at different pH values leads to the stabilization of three cerium‐based polyanionic molecular clusters [Ce3 (µ 2 ‐OH)3 (µ 3 ‐O)(SiW9 O34 )2 ] 13– (1 ), [Ce3 (µ 2 ‐O)3 (SiW9 O34 )2 ] 14– (2 ), and [Ce6 (µ 3 ‐O)4 (µ 3 ‐OH)4 ]2 (W8 O32 )(SiW9 O34 )4 32– (3 ). The condensation behavior of cerium in this kind of association with trivacant polyoxometalates (POMs) when a pH variation occurs is relatively unknown and needed to be explored. Compounds1 and2 consist of a trinuclear cerium cluster fragment stabilized by two POM moieties with a variation of the central cerium cluster from [Ce3 (µ 2 ‐OH)3 (µ 3 ‐O)] to [Ce3 (µ 2 ‐O)3 ]. Compound3 appears much more condensed with two hexanuclear [Ce6 (µ 3 ‐O)4 (µ 3 ‐OH)4 ] groups that are stabilized by the SiW9 O34 moieties and a W8 O32 tungsten ring. This evolution in cluster size and composition reflects the pH variation applied during their synthesis. The molecules have been characterized by single‐crystal X‐ray diffraction, 183 W and 29 Si NMR spectroscopy, IR spectroscopy, thermogravimetric analysis (TGA), and SEM/energy‐dispersive X‐ray (EDX) microscopy. The three compounds obtained here exemplify the influence of pH on the condensation of tetravalent cations and open a new route toward the stabilization of polynuclear tetravalent clusters by nucleophilic O‐donating POM species. Abstract : Increasing the pH during synthesis strongly influences the condensation behavior of cerium cations in association with the [α‐SiW9 O34 ] 10– heteropolyoxometalate, leading to the formation of trinuclear and hexanuclear Ce cores.